Effect of Trustworthiness of Internet Merchants on Consumer Trust in Online Shopping with the Moderating Effect of Perceived Risk (Global Journal of Management and Business Research, 2012)
Internet marketing has significantly changed the personality of store competition. More and more often, even normal customer not just the technical smart one is diving in over internet. The level to which the World Wide Web suppliers can build trust will considerably affect the desire to purchase over internet. Consequently it is important to understand the aspects that effect customer believe in e-retailers. Data was collected from five main universities of Islamabad i.e. Muhammad Ali Jinnah university, Islamic International, Comsats, Behria and Quaid.e.Azam university Islamabad. Snow ball sampling technique was used and 200 questionnaires were distributed of which 157 were returned. Result showed that trust of internet merchants does play a pivotal role in attracting customer to shop online. The finding of this research paper will help the internet marketers and merchants to device such strategies that can ensure consumer trust on e.retailers and hence lessen the risk being involved in online transaction.